2016
DOI: 10.1128/jvi.00658-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Ribose 2′- O -Methyltransferase Encoded by the Ronivirus Branch of Nidovirales

Abstract: The order Nidovirales currently comprises four virus families: Arteriviridae, Coronaviridae (divided into the subfamilies Coronavirinae and Torovirinae), Roniviridae, and the recently recognized Mesoniviridae. RNA cap formation and methylation have been best studied for coronaviruses, with emphasis on the identification and characterization of two virus-encoded methyltransferases (MTases) involved in RNA capping, a guanine-N7-MTase and a ribose-2=-O-MTase. Although bioinformatics analyses suggest that these MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…The corresponding regions of AAbV and the top protein BLAST match were then submitted to HHPred in align mode, which uses predicted structure and primary sequence data to compare proteins. This led to confident identifications of the NiRAN and a match for the divergent but functional 2O MTase domain of Gill-associated virus (Zeng et al, 2016). One other uncharacterized domain was also identified in both AAbV and TurrNV by protein BLAST, in the position where the coronavirus conserved replication accessory proteins nsp7-10 were expected ( Fig.…”
Section: Aabv Protein Bioinformaticsmentioning
confidence: 87%
“…The corresponding regions of AAbV and the top protein BLAST match were then submitted to HHPred in align mode, which uses predicted structure and primary sequence data to compare proteins. This led to confident identifications of the NiRAN and a match for the divergent but functional 2O MTase domain of Gill-associated virus (Zeng et al, 2016). One other uncharacterized domain was also identified in both AAbV and TurrNV by protein BLAST, in the position where the coronavirus conserved replication accessory proteins nsp7-10 were expected ( Fig.…”
Section: Aabv Protein Bioinformaticsmentioning
confidence: 87%
“…The importance of viral RNA modifications in replication has been supported by studies that the infection of viruses lacking 2 0 -O-methyltransferase activity induces higher type I IFN expression, and unmodified genomic RNA was recognized by the host RNA sensor, MDA5 (Zust et al, 2011). The functional importance of 2 0 -O-methyltransferase activity for the infectivity of RNA viruses was also verified by studies on dengue virus (DENV) (Zust et al, 2018), Middle East respiratory syndrome coronavirus (MERS-CoV) (Aouadi et al, 2017), and ronivirus (Zeng et al, 2016). These viruses also encode 2 0 -O-methyltransferase and its disruption also causes type I IFN induction and virus elimination from the host following infection.…”
Section: 0 -O-methyltransferasementioning
confidence: 93%
“…Although the (presumed) capping machinery of arteriviruses has remained essentially uncharacterized thus far (Lehmann et al, 2015b), three conserved putative capping enzymes were identified in the conserved ORF1b-encoded part of the replicase of Coronaviridae, Roniviridae, and Mesoniviridae, which all have substantially larger genomes. These enzymatic activities, which were proposed to participate in the synthesis of a cap-1 structure ( N7m GpppN 2 0 Om ), are the following: (i) the nsp13 helicase/RTPase (Ivanov and Ziebuhr, 2004), (ii) the nsp14 N7-MTase (Chen et al, 2009c;Ma et al, 2015), and (iii) the nsp16 2 0 -O-MTase (Bouvet et al, 2010;Decroly et al, 2008;Snijder et al, 2003;von Grotthuss et al, 2003;Zeng et al, 2016).…”
Section: The Coronavirus Capping Machinerymentioning
confidence: 99%